THE PROFESSIONALISM OF CERTIFIED TEACHERS: Loso Judijanto*, Melly Susanti - Judijanto, Loso; Susanti, Melly (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
Teacher certification is expected to improve teacher quality and raise education standards in the long term. This study aims to understand the professionalism of certified teachers. This method focuses on analyzing observed phenomena and generating complex structures that represent a particular reality. The main tool is the researcher, and the data collected is descriptive, giving more weight to the process than the outcome. The results show that the factors that contribute to the development of teacher professionalism are increasing teacher motivation, knowledge and skills, protecting the principal's control or supervision of various teacher activities, the principal's courage to be talented, mastering information technology. Principals strive to ensure certified teachers are responsible for their work, and if they fail to meet expectations, they risk having their teaching credentials revoked. They must also undergo training in making teaching materials, be proficient in information technology and conduct continuous assessment.